P3.105 Using Respondent-Driven Sampling to Estimate HIV and Syphilis Prevalence Among Female Sex Workers in Agadir, Fes, Rabat and Tangier, Morocco. (13th July 2013) - Johnston, L; Bennani, A; Latifi, A; Oumzil, H; Omari, B El; Rhoufrani, F El; Ouarsas, L; Alami, K; rhilani, H El
Abstract : Background: Throughout the world, including in the Middle East and North Africa region, female sex workers (FSW) often have a disproportionately high prevalence of HIV infection and they, along with their clients, are considered a core group contributing to the transmission of HIV in many countries. FSW, a highly stigmatised, hard-to-reach and understudied population in Morocco were surveyed in four cities in Morocco, using Respondent-Driven Sampling. Methods: 372 FSW in Agadir, 359 in Fes, 392 in Rabat and 324 in Tangier were sampled over the course of six to eight weeks in December 2011 and January 2012. Eligible females reported exchanging penetrative (vaginal/anal) sex for money with more than one male client in the past six months, being 18 years or older, holding Moroccan nationality and working in the respective study location. Estimates were calculated using the multiplicity estimator in RDSAT V.6.0. Results: Most FSW in all four cities had no or low education, were separated, divorced or widowed and financially supporting adults and/or children. HIV seroprevalence in Agadir was 5.1%, in Fes 1.8% and in Tangier 1.4%. No one tested positive for HIV in Rabat. Syphilis infection in Agadir was 21.4%, in Fes 18.8%, in Rabat 13.9% and in Tanger 13.3%. Conclusions: HIV among FSW in Morocco was lower than expected and confirms a concentrated epidemic in Agadir. Findings of syphilis infection among FSW may indicate infection with other sexually transmitted infections (STI) that were not tested in this survey and remain undetected. A scale up of programmes to provide targeted HIV outreach and services to FSW is essential to control the further spread of HIV and other STI in this population and to clients and other sexual partners.